Persulfidation alters gene regulatory programs and promotes endothelial specification - Wittig, Janina; Xu, Ran; Delgado Lagos, Fredy Andrés; Drekolia, Maria-Kyriaki; Zhang, Boran; Theodorou, Ioannis; Chen, Yunyun; Du, Yali; Gupta, Lavanya; Hanyu, Cui; Yuanyuan, Li; Bo, Cheng; et al. (Redox Biology, 2026)
Endogenously generated sulfides are conserved among species and tissues and exert multiple effects through diverse mechanisms. Although sulfides have been linked to cell fates, their role in pluripotent stem cell commitment remains unknown. Here we discovered that during directed differentiation of induced pluripotent stem cells, endogenous sulfide levels drop in all three germ layers, with the mesodermal lineage exhibiting the lowest capacity to generate these species at early specification events. Addition of a rapid releasing sulfide donor in iPSCs or mesodermal cells did not affect the redox surveillance mechanisms, however, it altered persulfidation and transcription of cell fate commitment pathways. In particular, sulfide supplementation in pluripotent stem cells reduced cell differentiation processes by preserving the activity of the stem cell transcription factors OCT4. In contrast, supplementation of sulfide during mesodermal lineage specification promoted persulfidation and activated the WNT signaling as well as enriched the activity of the ETS transcription factor family, resulting in increased transcription of angiogenic and vessel morphogenesis genes. Sulfide addition during the development of vascular organoids enhanced blood vessel morphogenesis. Taken together, these data position protein persulfidation as a timing-dependent regulator that preserves pluripotency prior to commitment but subsequently biases mesoderm toward endothelial specification, thereby emerging as a tractable redox modification for engineering stem cell fate and vascularization.